Analisis Sertifikasi Wakaf Masjid Al-Ihsaan di Kecamatan Cisurupan Kabupaten Garut Menurut Undang-Undang Wakaf No. 42/2004 - Hafesh Ash Shiddieqy Amrullah; Lis Sulistiani, Siska; Mujahid, Ilham (UNISBA Press, 2024)
Abstract. Waqf is not only understood in a spiritual dimension, but also contains a social dimension. However, the majority of people prefer to donate land and buildings to analyze the waqf mechanism for the Al-Ihsaan Mosque in Cisurupan District, Garut Regency and analysis of the certification of the Al-Ihsaan Mosque in Cisurupan District, Garut Regency according to the Waqf Law. The method used in this research is a qualitative research method with a normative juridical approach. The data sources used are primary, secondary and tertiary data. The results of this research are that after the waqf was pledged and the Waqf Pledge Deed was signed by the Wakif, the AIW was only published two weeks later. The official who made the Waqf Pledge Deed did not provide a cover letter for making the waqf land certificate to the National Land Agency. Nadzir did not receive a cover letter from the Office of Religious Affairs and there is no data base. In 2019, the Cisurupan KUA began to organize administration. By uploading all existing data, including inputting data on mosques under the auspices of KUA Cisurupan. So that every mosque has an ID. or the mosque's identity on the KUA website, but the Al-Ihsaan Mosque does not have an ID. Mosque. So the waqf process also experienced problems. Because the digital file does not exist and cannot be detected. So the Cisurupan District KUA proposed registering a Deed in Replacement of the Waqf Pledge Deed (APAIW). Abstrak. Wakaf tidak hanya dipahami dalam dimensi spiritual saja, melainkan juga mengandung dimensi sosial. Akan tetapi masyarakat mayoritas lebih suka mewakafkan tanah dan bangunan untuk menganalisis mekanisme wakaf Masjid Al-Ihsaan di Kecamatan Cisurupan, Kabupaten Garut dan analisis sertifikasi Masjid Al-Ihsaan di Kecamatan Cisurupan, Kabupaten Garut menurut Undang-Undang wakaf. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif dengan pendekatan yuridis normatif. Sumber data yang digunakan ialah data primer, sekunder dan tersier. Adapun hasil dari penelitian ini ialah Setelah wakaf diikrarkan dan Akta Ikrar Wakaf sudah ditantatangani oleh Wakif, AIW tersebut baru terbit dua minggu kemudian. Pejabat Pembuat Akta Ikrar Wakaf tidak memberikan surat pengantar untuk pembuatan sertifikat tanah wakaf ke Badan Pertanahan Nasional. Nadzir tidak menerima surat pengantar dari Kantor Urusan Agama dan tidak ada data base. Pada tahun 2019 KUA Cisurupan mulai mentertibkan administrasi. Dengan mengupload semua data yang ada, termasuk menginput data Masjid yang di bawah naungan KUA Cisurupan. Sehingga setiap Masjid memiliki ID. atau identitas Masjid di dalam website KUA, akan tetapi Masjid Al-Ihsaan pun tidak memiliki ID. Masjid. Sehingga dalam prosesi wakaf juga mengalami kendala. Karena berkas digitalnya tidak ada dan tidak bisa terdeteksi. Sehingga pihak KUA Kecamatan Cisurupan mengususlkan agar mendaftarkan Akta Pengganti Akta Ikrar Wakaf ( APAIW).